OsLRR-RLK1, an early responsive leucine-rich repeat receptor-like kinase, initiates rice defense responses against a chewing herbivore - Hu, Lingfei (The New phytologist, 2018)
© 2018 The Authors. New Phytologist © 2018 New Phytologist Trust.